Analysis of the Effect of Speech Therapy Services on Post-Stroke Patients' Quality of Life Through the Role of Family in Medical Rehabilitation - Zulva Rahma Laili; Joko Prasetyo; Agusta Dian Ellina (Indonesian Journal of Global Health Research, 2025)
Stroke is a neurological condition that often leads to brain dysfunction, resulting in paralysis, speech impairments, and a significant decline in patients' quality of life. Speech therapy is one of the critical rehabilitation methods to restore communication abilities in post-stroke patients, which subsequently improves their quality of life. Furthermore, family support plays a vital role in the success of rehabilitation, contributing emotionally, socially, and instrumentally. This study aims to analyze the effect of speech therapy services on the quality of life of post-stroke patients, with family involvement as a mediating variable. A quantitative research method with a cross-sectional design was employed. A total of 100 post-stroke patients undergoing medical rehabilitation were selected using purposive sampling. Data were collected through questionnaires. This study confirms the validity and reliability of the measurement scale, with all variables meeting convergent validity and composite reliability criteria. The data analyzed using path analysis to evaluate direct and indirect relationships between variables. The results revealed that speech therapy services significantly and positively impact patients' quality of life (p < 0.05). Family involvement was also found to have a significant impact, both directly on patients' quality of life and as a mediator that enhances the effectiveness of speech therapy services. The study concludes that optimal speech therapy services, combined with active family involvement, can significantly improve the quality of life of post-stroke patients. This study recommends increasing the number of speech therapists and actively involving families in rehabilitation programs for stroke patients at Ngudi Waluyo General Hospital.